The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s0103-50532006000700003
|View full text |Cite
|
Sign up to set email alerts
|

A novel Ho(III) sensor based on N,N'-bis(2- pyridinecarboxamide)-1,2-benzene as a neutral ion carrier

Abstract: N,N'-bis(2-piridinacarboxamida)-1,2-benzeno (H 2 BPB) apresentou um comportamento seletivo e sensível, frente ao íon Ho(III), em comparação a um grande número de íons de metais de transição interna, representativos e de lantanídeos, tendo sido portanto, aplicado como um ionóforo neutro para preparação de uma membrana sensora Ho(III), com alta seletividade e sensitividade. As membranas também contêm tetraquis(p-clorofenil) borato de potássio (KTpClPB) como um aditivo aniônico, e foram testadas pelo uso de difer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…The obtained selectivity coefficients revealed that these cations cannot disturb the function of the proposed Ho 3+ membrane sensor. Table 3 compared the detection limit, concentration range, response time, and selectivity coefficients for previously reported and proposed sensor [12][13][14][15][16][17]. As seen, the proposed membrane sensor based on H 2 Me 2 bpb shows superior selectivity to the previous reported ones.…”
Section: Determination Of the Selectivity Coefficientmentioning
confidence: 86%
See 2 more Smart Citations
“…The obtained selectivity coefficients revealed that these cations cannot disturb the function of the proposed Ho 3+ membrane sensor. Table 3 compared the detection limit, concentration range, response time, and selectivity coefficients for previously reported and proposed sensor [12][13][14][15][16][17]. As seen, the proposed membrane sensor based on H 2 Me 2 bpb shows superior selectivity to the previous reported ones.…”
Section: Determination Of the Selectivity Coefficientmentioning
confidence: 86%
“…Ionophores in references [13] and [14] cannot form a wrapped around complex. The ionophore used in references [15][16][17], are form a family. They are derivatives of symmetric picolinamide.…”
Section: Determination Of the Selectivity Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sensors include Eu 3+ [171,172], Gd 3+ [173][174][175][176], Tb 3+ [177,178], Dy 3+ [179,180], Ho 3+ [181,182], Er 3+ [183], Tm 3+ [184,185], Yb 3+ [186][187][188] PMEs, in addition to one Lu 3+ PME [189] and two uranyl PMEs and GCE [190,191]. The minimum detection limit among all of these sensors is reported to be 7.0 × 10 -8 for uranyl ion [191], which is a 2,2'- …”
Section: Cation Selective Sensorsmentioning
confidence: 99%
“…The potentiometric sensors based on ion-selective electrode are the best analytical method for such determination because they offer advantages such as selectivity, sensitivity, low detection limit, simplicity and low cost. [12][13][14][15][16][17][18][19][20][21][22][23][24] A literature survey reveled that few sensors [24][25][26][27][28][29][30][31] have been reported to determine Ho 3+ concentration, but they have low detection limit, narrow concentration range and interference from other ions. Thus, a quick, convenient, fast method is required to determine Ho 3+ in large number of environmental samples.…”
Section: Introductionmentioning
confidence: 99%